Radicalism in the Study of Philosophy - Rusly, Muhammad (Yayasan Sembilan Pemuda Indonesia, 2023)
The presence of diversity in Indonesia can potentially lead to the emergence of radical actions. This article provides information in the form of a review of radicalism in the field of philosophy, encompassing religious understanding, economics, politics, and education. The writing method is conducted through article review. Subsequently, it is found that religious radicalism is underpinned by the belief that their faith is the most correct and absolute. In economics, this is indicated by the rising unemployment rates, poverty, and social injustice, which can lead to economic disparities. In politics, it is demonstrated by the existence of several groups hoping to change the stable political system and social structure with new ideas they believe to be the most correct and suitable. In education, the problem can arise through interactions between teachers and students, students and teachers, as well as through the influence of parents and even society on components within the education system. Understanding radicalism in philosophical studies plays a crucial role in providing knowledge and becoming a solution to prevent and address radicalism, especially in Indonesia.